Regional mobility of unemployed workers. Experimental evidence on decision-making and behaviour in flexible labour markets. - Bähr, Sebastian (W. Bertelsmann, 2017)
Moderne Arbeitsmärkte erfordern ein hohes Maß an Flexibilität von Arbeitskräften und insbesondere von Arbeitslosen. Dabei kommt der Bereitschaft zur regionalen Mobilität im Zuge der tiefgreifenden Hartz-Reformen des deutschen Arbeitsmarktes eine zentrale Rolle zu. Vor diesem Hintergrund untersucht diese Forschungsarbeit die Bedeutung überregionaler Mobilität im Stellensuchprozess von Arbeitslosen. Basierend auf innovativen experimentellen Forschungsdesigns, reichhaltigen administrativen und Befragungsdaten und unter Verwendung aktueller ökonometrischer Analysen leistet der Autor einen wichtigen Beitrag zur aktuellen Debatte über die Wirkung von Flexibilisierung auf soziale Ungleichheit am Arbeitsmarkt.

Modern labour markets are characterised by the high levels of flexibility they demand of workers and unemployed individuals in particular. Increasing the willingness of jobseekers for regional mobility is an integral part of this development and was at the heart of the far reaching Hartz reforms of the German labour market in the early 2000s. Within this context, this research assesses the role regional mobility plays in the job search of unemployed individuals. Based on innovative experimental designs, rich administrative and survey data and state-of-the-art econometric analysis, the author contributes to the ongoing debate on flexibility induced inequality in the labour market.
Keywords: Arbeitsmarkt; Mobilität; Arbeitsloser; Flexibilität; Arbeitsplatz; Arbeitsuchender; Regionale Mobilität; Soziale Ungleichheit; Empirische Untersuchung